2010
DOI: 10.1523/jneurosci.5351-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 1 Mediates the Electrophysiological and Toxic Actions of the Cycad Derivative β-N-Methylamino-l-Alanine on Substantia Nigra Pars Compacta DAergic Neurons

Abstract: Amyotrophic lateral sclerosis-Parkinson dementia complex (ALS-PDC) is a neurodegenerative disease with ALS, parkinsonism, andAlzheimer's symptoms that is prevalent in the Guam population. ␤-N-Methylamino alanine (BMAA) has been proposed as the toxic agent damaging several neuronal types in ALS-PDC, including substantia nigra pars compacta dopaminergic (SNpc DAergic) neurons. BMAA is a mixed glutamate receptor agonist, but the specific pathways activated in DAergic neurons are not yet known. We combined electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 88 publications
(126 reference statements)
2
35
0
Order By: Relevance
“…These studies conflict with ours; our results, showing AMPA receptor activation, suggest that neuronal responses to D-Asp may depend on the receptor isoform expressed on each cell type. In support of this, we previously showed that another natural amino-acid, b-Nmethylamino-L-alanine (BMAA) activates different glutamate receptors in different brain areas: BMAA activates metabotropic/ AMPA receptors in nigral DAergic neurons (Cucchiaroni et al, 2010), NMDA receptors in cortical neurons (Lobner et al, 2007;Weiss et al, 1989) and AMPA/kainate receptors in spinal motoneurons (Rao et al, 2006).…”
Section: Glutamate Receptor Subtypes Contribute At Different Extent Imentioning
confidence: 84%
See 1 more Smart Citation
“…These studies conflict with ours; our results, showing AMPA receptor activation, suggest that neuronal responses to D-Asp may depend on the receptor isoform expressed on each cell type. In support of this, we previously showed that another natural amino-acid, b-Nmethylamino-L-alanine (BMAA) activates different glutamate receptors in different brain areas: BMAA activates metabotropic/ AMPA receptors in nigral DAergic neurons (Cucchiaroni et al, 2010), NMDA receptors in cortical neurons (Lobner et al, 2007;Weiss et al, 1989) and AMPA/kainate receptors in spinal motoneurons (Rao et al, 2006).…”
Section: Glutamate Receptor Subtypes Contribute At Different Extent Imentioning
confidence: 84%
“…By means of this technique, absolute current amplitude and kinetics may vary among neurons, depending on factors such as the distance of the recorded cell from the slice surface (where the agonist ejection occurs) or the route of aCSF flow which removes the agonist. However, this agonist application system elicits stable currents up to several minutes, being thus suitable for the pharmacological analysis (Cucchiaroni et al, 2010;Guatteo et al, 1999;Ledonne et al, 2015;Tozzi et al, 2001). Agonist-induced currents were recorded in control conditions or in the presence of MK-801 (30 mМ), CNQX (30 mМ) and CPCCOEt (100 mM), bath-applied for 9e12 min, or in DL-TBOA (100 mМ, bath-applied for 6 min).…”
Section: Drugsmentioning
confidence: 99%
“…Interestingly, GABAergic SNpc cells respond to BMAA with an AMPA-mediated inward current that is not associated with an intracellular calcium increase [Cucchiaroni et al 2010]. BMAA has been previously reported to activate mGluRs in hippocampal, striatal, and cerebellar neurons [Lobner et al 2007].…”
Section: Rotenonementioning
confidence: 99%
“…NMDA-evoked intracellular Ca 2þ overload is a major factor leading to excitotoxicity, by which neuronal apoptosis and necrosis occur in acute and chronic brain injuries and diseases, such as ischemia, trauma, epilepsy, amyotrophic lateral sclerosis, Alzheimer's disease and Parkinson's disease [19][20][21]. IL-6 attenuates glutamate-or NMDA-induced intracellular Ca 2þ overload and subsequently suppresses neuronal apoptosis and necrosis [14,18,22].…”
Section: Introductionmentioning
confidence: 99%